Educational Technology For Digital Learning : A Bibliometric Analysis - Sumarsono, Sumarsono; Husna Nur Syifana, Najwa (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the evolution of research in the field of educational technology using a bibliometric approach based on Scopus data. From an initial dataset of 9,783 articles, a systematic selection process using the PRISMA protocol narrowed the focus to 29 relevant articles for in-depth analysis. Utilizing VOSviewer software, the study explores keyword trends, co-authorship networks, and institutional as well as national affiliations involved in the field. The analysis reveals a growing interest in topics such as artificial intelligence, virtual reality, e-learning, and bibliometric methods within educational technology. In addition, the study identifies leading contributing countries, prominent research institutions, and highly cited papers. These findings provide a comprehensive overview of the recent developments in educational technology research. The implications of this study are expected to offer valuable insights for researchers and stakeholders in identifying research gaps and designing future research agendas that are more aligned with current technological and educational advancements.